Government Interventions during the Coronavirus Pandemic – A Critical Consideration - Florian W. Bartholomae; Eva Stumpfegger (CESifo Forum, 2021)
The coronavirus pandemic poses major challenges for governments. Especially in the beginning when news of the virus was breaking, information about the virus was limited. Many minor (e.g., facemasks) and major (e.g., curfews) restrictions were implemented to contain the virus. However, the German government failed at presenting a clear and targeted strategy, which led to confusing and overwhelmingly detailed regulations that did not entail suitable cost-benefit considerations. Many costs occurred as a consequence of the measures that were instituted (e.g., government aid for forced shop and restaurant closures). In addition, asymmetric interventions severely impacted the economic structure of and the careers, for example, those in the hospitality industry. We suggest that the government focus on more general recommendations for action based on sound information, which would then provide an appropriate framework for the markets.
Keywords: 330